The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.4049/jimmunol.1501037
|View full text |Cite
|
Sign up to set email alerts
|

Dok1 and Dok2 Proteins Regulate Cell Cycle in Hematopoietic Stem and Progenitor Cells

Abstract: Dok1 and Dok2 proteins play a crucial role in myeloid cell proliferation as demonstrated by Dok1 and Dok2 gene inactivation, which induces a myeloproliferative disease in aging mice. In this study, we show that Dok1/Dok2 deficiency affects myeloproliferation even at a young age. An increase in the cellularity of multipotent progenitors is observed in young Dok1/Dok2-deficient mice. This is associated with an increase in the cells undergoing cell cycle, which is restricted to myeloid committed progenitors. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…The number of total mononuclear cells, Lin À Sca1 + c-Kit + cells, and Lin À Sca1 À c-Kit + myeloid progenitors (MPs) in the bone marrow of Spib À/À mice was comparable to WT mice ( Figures 3B and 3C). MPs are further divided into CMP, GMP, and MEP based on the expression of CD34 and FcgRII/III (Coppin et al, 2016). While these three progenitors were numerically similar in WT bone marrow, there were more GMP and fewer MEP in the Spib À/À mice ( Figures 3C and 3D).…”
Section: Spi-b Deficiency Results In Expansion Of Mast Cells Due To Amentioning
confidence: 99%
“…The number of total mononuclear cells, Lin À Sca1 + c-Kit + cells, and Lin À Sca1 À c-Kit + myeloid progenitors (MPs) in the bone marrow of Spib À/À mice was comparable to WT mice ( Figures 3B and 3C). MPs are further divided into CMP, GMP, and MEP based on the expression of CD34 and FcgRII/III (Coppin et al, 2016). While these three progenitors were numerically similar in WT bone marrow, there were more GMP and fewer MEP in the Spib À/À mice ( Figures 3C and 3D).…”
Section: Spi-b Deficiency Results In Expansion Of Mast Cells Due To Amentioning
confidence: 99%
“…Tumor suppressing roles of DOK1 / 2 have been reported in solid tissues and hematopoietic compartment in several studies (Berger et al, ; Coppin et al, ; Ghanem, Bracken, Kasem, Jiang, & Mokbel, ; Lee et al, , 2007; Niki et al, ; Yasuda et al, ). Genetic disruption of DOK1 / 2 in animal models and human tumor samples increased their susceptibility to leukemia development (Celis‐Gutierrez et al, ; Coppin et al, ; Mashima et al, , ; Niki et al, ; Yasuda et al, ). Niki et al () and Yasuda et al () through functional studies in vivo revealed that DOK1 / 2 inactivation resulted in hyperplasia of myeloid progenitors at various stages and markedly accelerated leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…Downstream of tyrosine kinase ( DOK ), a large family of phosphotyrosine adapters, are substrates of protein tyrosine kinases (Coppin et al, ). Seven members ( DOK1 – DOK7 ) of DOK family have been identified, and these members were found to be implicated in the regulation of multiple biological processes, including cell growth, transformation, differentiation, motility, and death (Celis‐Gutierrez et al, ; Mashima, Hishida, Tezuka, & Yamanashi, , Mashima et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…These two closely related Dok family members are involved in the regulation of several cellular processes, such as proliferation, differentiation, and migration. Using Dok-1-and -2 (Dok-1/2)-deficient mice, biological roles for Dok-1 and Dok-2 have been demonstrated in antibody responses to thymus-dependent antigens, NK and hematopoietic cell development and function, innate immune response to lipopolysaccharide (LPS), myeloid homeostasis, and leukemia suppression (29)(30)(31)(32)(33)(34)(35)(36). In addition, we recently demonstrated that Dok proteins regulate the CD8 ϩ T cell response to an exogenous epitope expressed by vaccinia virus (VV) (37).…”
mentioning
confidence: 99%